2019
DOI: 10.1186/s13102-019-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal jumping biomechanics among elite female handball players with and without anterior cruciate ligament reconstruction: an ISU based study

Abstract: BackgroundHandball is a strenuous body-contact team sport that places high loads on the knee joint. Anterior cruciate ligament (ACL) tear is one of the most devastating injuries that any handball player can suffer, and female athletes are at particular risk due to their intrinsic anatomical, hormonal, neuromuscular and biomechanical characteristics. The purpose of this study was to analyze the horizontal jumping biomechanics of female elite handball players with or without previous ACL reconstruction.MethodsTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, as the ISU is placed on the subject s center of mass location at the lumbar spine, no conditioned foot placement is needed, preserving the ecological environment of the player keeping her closer to a real-game situation. Previous research has demonstrated lower mechanical efficiency ratios among male and female [37] handball players with previous ACL reconstruction in comparison to age-, sex-, and competition level-matched controls in horizontal jumping maneuvers.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, as the ISU is placed on the subject s center of mass location at the lumbar spine, no conditioned foot placement is needed, preserving the ecological environment of the player keeping her closer to a real-game situation. Previous research has demonstrated lower mechanical efficiency ratios among male and female [37] handball players with previous ACL reconstruction in comparison to age-, sex-, and competition level-matched controls in horizontal jumping maneuvers.…”
Section: Discussionmentioning
confidence: 89%
“…Total jump length was recorded (TJL) [35]. Kinetic data was registered using the IMU technology described above and based on a previously validated methodology [37].…”
Section: Jumping Biomechanics Assessmentmentioning
confidence: 99%
“…1). Twelve were removed after the full-text screening (Armitano et al, 2017;Dowling et al, 2011Dowling et al, , 2012Fong et al, 2011;Hohmann et al, 2015;Kim et al, 2018;Reenalda et al, 2018;Setuain et al, 2015bSetuain et al, , 2019aSetuain et al, , 2019bSkvortsov et al, 2020;Tsuruoka et al, 2005). Eleven studies remained and were included in this scoping review (Bailey et al, 2016;Dan et al, 2019;Havens et al, 2018;Kim et al, 2020;Peebles et al, 2019a;Sigward, 2018a, 2018b;Setuain et al, 2015a;Sigward et al, 2016;Thomson et al, 2018;Vervaat et al, 2020).…”
Section: Identification Of the Studiesmentioning
confidence: 99%
“…In particular, side-cutting movements and one-legged landing manoeuvres that are common in handball create a high external knee valgus moment that has been shown to predispose the knee to Anterior Cruciate Ligament (ACL) tear [3][4][5][6]. Female handball players are more likely to sustain an ACL injury compared to their male counterparts, and the overall rate of ACL injury in handball is 0.86 injuries for female and 0.24 for male players per 1000 hours of exposure [7,8]. ACL injuries are of particular interest because they can be a devastating injury for the health and the career of an athlete.…”
Section: Introductionmentioning
confidence: 99%